PROFITABILITY OF ORGANIC YELLOW PASSION FRUIT AS A FUNCTION OF IRRIGATION, PROTECTED CULTIVATION AND POLLINATION - Silva, Nilciléia Mendes da (2022)
Passion fruit production has become an attractive activity due to its social and economic benefits, given the rapid economic return and well-distributed income over most of the year. From this perspective, this study aimed to evaluate the technical and economic indicators of yellow passion fruit cultivation by combining irrigation, protected cultivation, and pollination. The experimental design was in randomized blocks set up in split plots (2 x 2 x 2), with eight treatments and four replicates containing four plants per experimental unit. The protected environment was installed on the upper part of each trellis and consisted of 100 m transparent plastic film as cover material. Irrigation was performed using a micro-sprinkler system, and pollination was either manual or natural (entomophilous). The following parameters were evaluated: commercial yield - estimated for one hectare considering the mass of marketable fruits produced in the plot (30 m2); production cost - capital depreciation, input prices, and labor used in cultivation; economic indicators - profitability index, family labor remuneration, profitability, net income, benefit/cost ratio, and fixed, variable, and total costs. The results show that artificial pollination increased the yield and provided a 41% higher profitability rate than natural pollination; supplemental irrigation, compared to rainfed cultivation, has no positive effects on profitability indices; protected cultivation increases the total cost and does not increase the yield; organic passion fruit production provides profitability indices ranging from 60% to 70%.